Application of adsorption potential theory in prediction of CO and CH adsorption on carbon molecular sieves - Xue Song; Li’ao Wang; Yifu Li; Yunmin Zeng; Xinyuan Zhan; Jian Gong (Adsorption Science & Technology)
The adsorption of CO 2 and CH 4 on carbon molecular sieves was studied based on the adsorption potential theory, which is widely used in gas adsorption on microporous adsorbents. The methods to obtain the adsorption density in the adsorbed phase, including Ozawa’s method and the empirical method, and the methods to calculate the virtual saturation vapor pressure, including Dubinin’s method and Amankwah’s method, were discussed. A functional exponential form proposed in this study could describe the adsorption characteristic curve better than the cubic polynomial and logarithmic function used in the previous literature. A new model, which expresses the correlation of adsorbed amount, temperature, and pressure, was proposed and verified experimentally. The model provides a reliable way to predict the adsorption isotherms of CO 2 and CH 4 on carbon molecular sieves at different temperatures according to the data measured at a certain temperature and to select a proper kind of carbon molecular sieve in CO 2 /CH 4 separation.